2018
DOI: 10.3389/fmicb.2018.01270
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces spp. From Ethiopia Producing Antimicrobial Compounds: Characterization via Bioassays, Genome Analyses, and Mass Spectrometry

Abstract: A total of 416 actinomycete cultures were isolated from various unique environments in Ethiopia and tested for bioactivity. Six isolates with pronounced antimicrobial activity were chosen for taxonomic identification and further investigation. Morphological and cultural properties of the isolates were found to be consistent with those of the genus Streptomyces, which was further confirmed by phylogenetic analysis based on 16S rRNA gene sequences. One of the isolates, designated Streptomyces sp. Go-475, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…eir ability to produce urease can be exploited to enrich and isolate such bacteria from the environment for future applications [21]. While the occurrence of these bacteria and their characteristics have been explored in some regions and soil types [1,12,21,22] and other novel bacterial strains isolated from Ethiopian sediments and soils [23,24], this study is the first report on the characterization of ureolytic bacteria from Ethiopian soil. is study aimed to isolate and characterize rapid ureaseproducing bacteria from Ethiopian soils.…”
Section: Introductionmentioning
confidence: 99%
“…eir ability to produce urease can be exploited to enrich and isolate such bacteria from the environment for future applications [21]. While the occurrence of these bacteria and their characteristics have been explored in some regions and soil types [1,12,21,22] and other novel bacterial strains isolated from Ethiopian sediments and soils [23,24], this study is the first report on the characterization of ureolytic bacteria from Ethiopian soil. is study aimed to isolate and characterize rapid ureaseproducing bacteria from Ethiopian soils.…”
Section: Introductionmentioning
confidence: 99%
“…However, their isolates were not able to inhibit the growth of E. coli and P. aeruginosa [13] . Moreover, Kibret et al [14] detected 416 isolates of Streptomyces with certain bacterial members, such as their designated Go -475 isolate, with strong bioactive cross -product substances, some of them are newly identified, that decreased the livability of some fungi and Gram positive pathogenic bacteria. In addition, they found that the DNA gnomic materials have the ability to code for antimicrobial metabolites [14] .…”
Section: Discussionmentioning
confidence: 99%
“…If the coverage was above 10, the minimum frequency was 90% instead. Additionally, genomic DNA of C. glutamicum ∆ald ∆fadH ∆rpe strains MDS2, MDS2T8 and MDS2T14 was sequenced using Nanopore MinION sequencing technology (Oxford Nanopore Technologies Oxford, UK) as described previously [53]. After assembly, 11 contigs for MDS2, 6 contigs for MDS2T8 and 2 contigs for MDS2T14 were revealed.…”
Section: Whole-genome Sequencingmentioning
confidence: 99%